INTEGRATION OF NEUROMARKETING TECHNOLOGIES INTO THE E-COMMERCE ECOSYSTEM: ANALYSIS OF INCREASING CONVERSION AND USER EXPERIENCE USING THE EXAMPLE OF THE LARGEST ONLINE PLATFORMS (Marketing Journal, 2025)
The article analyzes the strategic application of interdisciplinary neuromarketing methods within the highly competitive environment of modern digital marketplaces such as Wildberries, Uzum Market, and Yandex.Market. Neuromarketing, which integrates advancements in neuroscience and marketing, enables the study of consumers’ subconscious (implicit) reactions and is increasingly used in e-commerce. The study provides an overview of current literature on neuromarketing and its role in online commerce, including the “Marketing 5.0” concept. Core methodological tools such as fMRI, EEG, and eye-tracking, along with complementary biometric technologies used to assess user experience (UX) and cognitive load, are described. 24 Applied cases demonstrating neuromarketing -driven interface optimization are examined, showing how such improvements enhance conversion rates and consumer loyalty through deeper behavioral insights. Special attention is given to ethical standards and data confidentiality when collecting and utilizing neurophysiological information. The article explores practical applications of neuromarketing across leading marketplaces and highlights modern trends such as personalization, emotional triggers, and real-time data analytics. It is emphasized that neuromarketing enhances conversion and loyalty by providing a deeper understanding of consumer behavior. The conclusion summarizes case findings, their impact on buyer behavior and performance indicators, and offers recommendations for future research and ethical considerations.
Keywords: neuromarketing; consumer behavior; fMRI; EEG; eye-tracking; emotional triggers; marketing strategies; subconscious decision -making; ethical considerations; digital technologies